2015
DOI: 10.1200/jco.2014.58.9093
|View full text |Cite|
|
Sign up to set email alerts
|

Complete Regression of Metastatic Cervical Cancer After Treatment With Human Papillomavirus–Targeted Tumor-Infiltrating T Cells

Abstract: Purpose Metastatic cervical cancer is a prototypical chemotherapy-refractory epithelial malignancy for which better treatments are needed. Adoptive T-cell therapy (ACT) is emerging as a promising cancer treatment, but its study in epithelial malignancies has been limited. This study was conducted to determine if ACT could mediate regression of metastatic cervical cancer. Patients and Methods Patients enrolled onto this protocol were diagnosed with metastatic cervical cancer and had previously received platinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
411
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 542 publications
(421 citation statements)
references
References 37 publications
4
411
1
5
Order By: Relevance
“…Acknowledgement of vaccinator training for safe vaccine administration and reassurance of expected minor adverse effects including injection site pain should be included in public education campaigns [37]. Peruvians' awareness that vaccines may be preventive or therapeutic will be beneficial in the future should the therapeutic vaccines and adoptive T-cell therapies currently under investigation for cervical intraepithelial neoplasia 2/3 and CC treatment reach the market [44,45].…”
Section: Means For Changing Attitudes Towards Hpv Vaccinationmentioning
confidence: 99%
“…Acknowledgement of vaccinator training for safe vaccine administration and reassurance of expected minor adverse effects including injection site pain should be included in public education campaigns [37]. Peruvians' awareness that vaccines may be preventive or therapeutic will be beneficial in the future should the therapeutic vaccines and adoptive T-cell therapies currently under investigation for cervical intraepithelial neoplasia 2/3 and CC treatment reach the market [44,45].…”
Section: Means For Changing Attitudes Towards Hpv Vaccinationmentioning
confidence: 99%
“…Since most gastric LELCs contain the EBV oncoproteins, and cancer-driving viral antigens are highly attractive therapeutic targets, therapeutic vaccines targeting the EBV oncoproteins may prove to be beneficial. Furthermore, adoptive T-cell therapy is emerging as a promising cancer treatment, and one recently published study demonstrated that durable, complete regression of metastatic cervical cancer may occur after a single infusion of HPV-targeted tumor-infiltrating lymphocytes (TILs) (18). Hence, we must investigate whether an infusion of EBV-targeted TILs may induce cancer regression in patients with gastric LELC.…”
Section: Discussionmentioning
confidence: 99%
“…In CC a large polyclonal repertoire of T cells HPVspecific have been demonstrated within the total population of TILs as well as in tumor-draining lymph nodes (de Vos van Steenwijk, 2010). In a therapeutic approach, objective regression of metastasis in CC patients by HPV-TILs enables to discuss about their immunological role, which could explain more aggressive behavior in HPV-negative tumors and encourages research for immunotherapy strategies in CC (Stevanović, 2015).…”
Section: Discussionmentioning
confidence: 99%